2019
DOI: 10.1186/s12879-019-3968-5
|View full text |Cite
|
Sign up to set email alerts
|

Talaromyces marneffei infection in a lung cancer patient: a rare case report

Abstract: Background Talaromyces marneffei is an invasive, and thermal dimorphic pathogenic fungus, whose infection is life threatening in human . Although immunocompromised patients, such as patients with human immunodeficiency virus infection and recipients of organ transplant, are susceptible hosts, infections have been recently reported in people with normal immune function. Patients with cancer may also be susceptible hosts but no case of T. marne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 8 publications
1
5
0
Order By: Relevance
“…Only the yeast phase has pathogenicity. In addition, a mulberry-shaped cell mass, sausage-shaped cells, and a transverse wall are the three main morphological characteristics of T. marneffei growth in tissue, 11 which were also found in our case.…”
Section: Discussionsupporting
confidence: 84%
“…Only the yeast phase has pathogenicity. In addition, a mulberry-shaped cell mass, sausage-shaped cells, and a transverse wall are the three main morphological characteristics of T. marneffei growth in tissue, 11 which were also found in our case.…”
Section: Discussionsupporting
confidence: 84%
“…Our literature review identified few cases of lung cancer with Talaromycosis (8,11). Lung cancer will impair the immune system, but whether this is an important cause of Talaromycosis remains to be confirmed by future studies.…”
Section: Discussionmentioning
confidence: 99%
“…For TSM patients presenting with multiple osteolysis and/or swollen lymph nodes, hematologic malignancies should be considered if active antifungal therapy proves to be ineffective. For patients with cancer, such as hematological malignancies and lung cancer [ 9 ], the presence of TM should be ascertained before or after chemotherapy. The final diagnosis primarily relies on multiple pathological examinations and the pathogenic culture of lymph nodes and bone marrow tissue.…”
Section: Discussionmentioning
confidence: 99%